Background Characteristics and Oral Proficiency Development Over Time in Lower‐Division College Foreign Language Programs. Issue 3 (20th April 2020) - Zhang, Xiaowan; Winke, Paula; Clark, Shaunna
Abstract: Answering calls to map college‐level proficiency development (Modern Language Association, 2007) and longitudinally chart language learning (Barkaoui, 2014; Ortega & Byrnes, 2008), we mapped the oral proficiency growth of 1, 922 lower‐division college students of Chinese, French, Russian, and Spanish (in the second, third, or fourth semester of their programs), using the Oral Proficiency Interview–computer (OPIc). We recorded students' gender, heritage‐learner status, high school language experience, interest in learning the target language, perceived importance of speaking, and outside‐of‐class second language (L2) contact, in order to differentiate growth. Latent growth curve analyses showed that learners' oral proficiency progressed at an average rate of one sublevel per year on the scale of the American Council on the Teaching of Foreign Languages (2012), following a nonlinear developmental path that was mildly accelerating over time. Students' proficiency development had a significant relationship with the language being learned, heritage‐learner status, high school language experience, interest in learning, and perceived importance of speaking. No unique effects were found for gender or out‐of‐class L2 contact. Abstract :